(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Density functional theory calculations have been performed with B3LYP functional and 6-311+G(d,p) basis set implemented in the Gaussian 09 package inorder to support spectral characteristics and geometry of triflusulfuron-methyl, a molecule known for its herbicidal activity. The observed Raman and infrared spectral bands have been assigned in the framework of theoretical frequencies and intensities. Aromaticity of the phenyl and triazine rings has been measured based on harmonic oscillator model of aromaticity index. Natural bond orbital analysis performed on triflusulfuron-methyl has been carried out to reveal various nonbonding interactions present in the molecule. Triflusulfuron-methyl has been tested for its antimicrobial activity and found to exhibit antifungal and antibacterial effects.